The chef - Patterson, James, 1947-; DiLallo, Max (New York : Little, Brown and Company, 2019)
c
Includes recipes.
Keywords: Police -- Louisiana -- New Orleans -- Fiction; Cooks -- Fiction; Murder -- Investigation -- Fiction; New Orleans (La.) -- Fiction; Detective and mystery fiction; Thrillers (Fiction).